Analisis Universalitas Penggunaan Kata “anu” dalam Perspektif Filsafat Bahasa: Analysis of the Universality of the Use of the Word "anu" in the Perspective of Language Philosophy - Putawa, Rilliandi Arindra (Jurnal Filsafat Indonesia, 2024)
This article is a study in the field of philosophy that seeks to trace the meaning and usage of the word "anu" from the perspectives of the three main branches of philosophy, namely metaphysics, epistemology, and axiology. The researcher employs a literature review method by examining various previous studies on the usage of the word "anu" in society and also the theories of the three main branches of philosophy. The material object, which in this case is the word "anu," is then examined from the perspectives of the three main branches of philosophy. Based on the conducted research, it is known that the word "anu" does not meet the requirements as the most universal concept, as does the word "ada." The set of words "anu" is highly limited by the level of knowledge of the users and also the norms of politeness. On one hand, this word is in line with what Wittgenstein conveyed in the theory of language games, but on the other hand, in terms of universality, the existence of the word "anu" is questioned by two metaphysical streams, namely realism and nominalism, both of which agree not to accommodate the word "anu." The word "anu" cannot be a universal predicate inherent in objects and also contradicts the particular principle of nominalism.